Identical molecular strings woven differently by intermolecular interactions in dimorphs of myo-inositol 1,3,5-orthobenzoate - Bhosekar, Gaurav V.; Murali, Chebrolu; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2005)
myo-Inositol 1,3,5-orthobenzoate exhibits polymorphic behavior depending upon the solvent and time allowed for crystallization. Long plates (form I, monoclinic P2(1)/n) are produced on crystallization from methanol, while crystallization from ethyl acetate mostly yielded squarish plates (form II, monoclinic P2(1)/c). The latter could also be obtained by achieving rapid nucleation from a supersaturated solution of methanol. Remarkably, the overall conformation of the individual molecules is very similar in both polymorphs, although free rotations were possible for the phenyl ring and for the three O-H groups. O-H center dot center dot center dot O linked one-dimensional isostructural molecular strings in the two forms weave differently by weak intermolecular interactions to produce the dimorphs. Striking difference is seen in the ``zipping'' of molecular layers via phenyl center dot center dot center dot phenyl contacts; thermodynamic crystals of form I utilize a well-recognized ``edge-to-face'' herringbone pattern, making C-H center dot center dot center dot pi interactions, whereas the kinetic crystals of form II show rather uncommon ``edge-to-edge'' organization, which makes short Ph-H center dot center dot center dot H-Ph contacts.

Investigating organization of molecules that facilitates intermolecular acyl transfer in crystals: reactivity and x-ray structures of O-benzoyl-myo-inositol 1,3,5-orthoesters - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (European Journal of Organic Chemsitry, 2007)
{Crystal structure analysis of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate reveals helical organization of the molecules, remarkably similar to that observed earlier in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate. Both these dibenzoates are isostructural despite the bulkier phenyl substituent in place of hydrogen. The latter compound shows highly facile intermolecular benzoyl transfer reactivity in its crystals and as anticipated from the crystal structure, the orthobenzoate indeed exhibits facile benzoyl transfer reactivity in its crystals. 2-O-Benzoyl-myo-inositol 1,3,5-orthoformate and the corresponding orthobenzoate also undergo transesterification in their crystals, but the specificity of acyl transfer is very low, and the reaction yields a mixture of products. The parameters of helical molecular assembly that facilitates acyl transfer in crystals have been investigated. A comparison of the molecular assemblies and lattice interactions in crystals of all the four compounds with the observed reactivity patterns show that facile acyl transfer reaction is brought about by a modular ``reaction tunnel''
Keywords: AOT; CdS-Ag2S; core-shell; Nanoparticles; w/o microemulsion; XPS

Intramolecular hydrogen abstraction in radicals derived from inositol 1,3-acetals: efficient access to cyclitols - Murali, Chebrolu; Gurale, Bharat P.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
The benzylidene acetals obtained by cleavage of the orthobenzoate moiety in myo-mositol 1,3,5-orthobenzoate were used to prepare mono- as well as di-deoxy inositol derivatives via their xanthates. The dideoxygenation is a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Such a cleavage does not take place in analogous acetals derived from other orthoesters. The 1,3-acetals derived from myoinositol 1,3,5-orthoesters were also used to prepare neo-inositol and isomeric deoxy-amino inositols, Most of the reactions in these synthetic sequences starting from myo-inositol give one product in each step. The results presented here show that myo-inositol 1,3,5-orthobenzoate offers many advantages over other orthoesters for the synthesis of cyclitol derivatives from myo-inositol.
Keywords: cyclitols; Deoxygenation; Inosamine; Inositol; Radical reactions; Radicals; Xanthate